Techniques of Translating Indonesian Legal Texts into English - Ana, I Wayan; Puspani, Ida Ayu Made (e-Journal of Linguistics; Vol 15 No 2 (2021): e-jl JulyDO - 10.24843/e-jl.2021.v15.i02.p09, 2021)
Translation techniques are skills, practical arts or procedures used by translators in their translation activities. Translation techniques are applied to assist translators to select the most precise and accurate equivalents in Target Language (TL). This study was carried out to find the techniques used by legal translators in translating legal text. The data for this study were taken from Law No. 25 of 2007 and four notary deeds and two non-notary deeds. The data were qualitatively analyzed based on the theory of translation procedures by Newmark (1988). The result of this study showed that fifteen translation techniques were used by legal translators. Literal translation occupies the top position, followed by calque, pragmatic amplification, established equivalence, translation shift, reversed naturalization, generalization, pragmatic reduction, modulation, compensation, semantic compression, cultural adaptation, borrowing, semantic amplification and description. The result of this study denied Alcaraz and Hughes’ argument that literal translation is not recommended in the translation.